DARI DARING KEMBALI KE LURING: PERSPEKTIF MASYARAKAT SIBER MENGENAI IMPLEMENTASI PENDIDIKAN FORMAL SELAMA PANDEMI COVID-19 DI INDONESIA - Cut Meutia Karolina; Irwa Rochimah Zarkasi (Kinesik, 2023)
The process of learning methods for formal education during COVID-19 in Indonesia experienced the dynamics of pros and cons in the society, especially for parents who faced changes in learning methods for their children. The purpose of this research is to find out how the cyber community responses to the planned change in learning methods from online, which then returns to offline during the pandemic. This study uses a qualitative method with netnographic approach. This research involves several theories: participatory culture, symbolic interaction and the concept of debating in cyberspace. The results of this study reveal three perspectives on responding to this issue. Social media, especially Instagram, is a forum for public expression regarding an issue in society that should not be ignored. Many important views are conveyed through social media. The pros and cons are based on various points of view. The unique finding of this study is a personal attack on dissent.